(untitled) - Williams, Patrick (New Jersey, 2006)
"This book provides an easy-to-read introduction to the core ethical and professional issues faced by all coaches irrespective of length of coaching experience. The case studies and guidelines in this book will help coaches constructively reflect on their coaching practice, and will help build the solid ethical foundation that professional coaching practice demands. A very useful text for both the beginning and experienced coach."
Keywords: Personal coaching,Executive coaching; Practice,Practice